2009
DOI: 10.1002/jcla.20311
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of extracts of Jatropha curcas and Moringa oleifera in culture media for selective inhibition of saprophytic fungal contaminants

Abstract: Most fungi occur in nature and utilize simple sources of carbohydrates and nitrogen for growth. Sabouraud's dextrose agar has been an ideal medium for primary isolation of fungi from clinical specimens, but for specimens from nonsterile sites or heavily contaminated ones, it has been necessary to include inhibitory substances such as antibiotics like chloramphenicol (antibacterial) and cycloheximide (antifungal). The problems we have in the our laboratory owing to frequent contamination of cultures and the del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 4 publications
1
11
0
1
Order By: Relevance
“…The nutritional properties of leaves and seeds of M. oleifera were shown by Sreelatha and Padma (2009) and Afuang et al (2003). Thirty-four diseases are treated with various products of M. oleifera, as shown by the works of several authors who provide a scientific basis of these uses (Anwar et al 2006, Anwar et al 2007, Ayanbimpe et al 2009, Beltrán-Heredia et al 2009, Gilani et al 1994, Kalogo et al 2000, Kumar et al 2007, Lea 2010. The massive use of leaves in human and animal nutrition and in traditional medicine implies premature and continuing harvests, which constitutes a pressure on the foliar biomass and consequently on the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional properties of leaves and seeds of M. oleifera were shown by Sreelatha and Padma (2009) and Afuang et al (2003). Thirty-four diseases are treated with various products of M. oleifera, as shown by the works of several authors who provide a scientific basis of these uses (Anwar et al 2006, Anwar et al 2007, Ayanbimpe et al 2009, Beltrán-Heredia et al 2009, Gilani et al 1994, Kalogo et al 2000, Kumar et al 2007, Lea 2010. The massive use of leaves in human and animal nutrition and in traditional medicine implies premature and continuing harvests, which constitutes a pressure on the foliar biomass and consequently on the species.…”
Section: Discussionmentioning
confidence: 99%
“…In assessing the inhibition potential of combined extracts of J. curcas and M. oleifera on saprophytes and fungal contaminants, Ayanbimpe et al (2009) concluded that these easily accessible, cheap extracts could be substitutes for antibiotics and antifungals frequently used in laboratories such as chloramphenicol and cycloheximide. However, in spite of these authors' interest in nutritional and medicinal aspects of M. oleifera, their work did not address traditional methods of use, manufacture of remedies, or dosages.…”
Section: Introductionmentioning
confidence: 99%
“…Saprophytic fungi were also found to be inhibited by the extract of Moringa oleifera leaves [30]. This antifungal property of Moringa oleifera can prevent culture media contaminations by some saprophytic fungi.…”
Section: Antifungal Activity Of Moringa Oleiferamentioning
confidence: 82%
“…Leaves Ethanol extract Antibacterial activity [10][11][12] Antisaprophytic fungi activity [30] Anti-HSV activity [37] Methanol extract Antileishmanial activity (IC50=47.5 ug/ml) [41] Niaziminin Inhibit the activation of EBV in Raji cells [36] Niazinin Antileishmanial activity (IC50=1.8ug/ml) [41] Silver nanoparticles Antibacterial activity [26] …”
Section: Tissues Compounds Activities Referencesmentioning
confidence: 99%
“…6 This toxicity of the seed is attributed predominantly to the phorbol-type diterpene esters which they contain at high concentrations. 7 Previous studies on leaves of this plant have investigated the isolation of flavonoids, 8 sterols, 9 polyprenols, 10 besides saprophytic fungal activity, 11 larvicidal activity, 12 and molluscicidal activity. 13 As a part of an ongoing study toward biorational control of S. frugiperda, 14 the aim of the present work was to chemically investigate and evaluate the insecticidal activity of extracts from the leaves of J. curcas accession (bout) against the larvae of fall armyworm under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%